Inversion of backscatter ionograms and TEC data for over-the-horizon radar - Fridman, Sergey V.; Nickisch, L. J.; Hausman, Mark (Radio science, 2012)
Over‐the‐horizon radar (OTHR) uses ionospheric reflection to propagate HF transmissions to long range (∼500–5000 km). The ionosphere acts as a dynamic “mirror” that varies diurnally, seasonally, and with the solar cycle. Geolocation of targets observed by OTHR (Coordinate Registration (CR)) requires accurate real‐time ionospheric modeling and HF propagation calculations to convert radar‐measured target signal delays and beam steers to geographical position. We merged our backscatter ionogram (BI) leading edge inversion algorithm CREDO with our more advanced ionospheric data assimilation capability, GPS Ionospheric Inversion (GPSII). The combined algorithm produces a dynamic model of electron density for a fixed geographical region. The model is consistent with BI leading edge data, vertical sounding data, as well as with absolute and relative total electron content (TEC) data from a number of GPS/LEO receivers. Incorporation of additional ionospheric data beyond conventional OTHR vertical and oblique backscatter soundings is expected to enhance the fidelity of real‐time ionosphere models, resulting in improved OTHR Coordinate Registration metric accuracy. Initial tests of the OTHR CR supported by the new ionospheric inversion algorithm indicate noticeable improvement of CR accuracy in comparison with legacy techniques. Key Points OTHR coordinate registration requires real‐time ionosphere model Ionospheric model supported by backscatter and vertical ionograms is useful Ionospheric model is further improved by incorporating GPS TEC data